Konsumsi Dark Chocolate Berpengaruh dalam Menurunkan Tingkat Kecemasan Atlet Taekwondo Bondowoso Sebelum Ujian Kenaikan Tingkat - Fayza Wara Az Zahra; Cleonara Yanuar Dini (Yayasan Literasi Sains Indonesia, 2026)
Anxiety is a psychological condition frequently experienced by athletes when facing evaluative situations or competitive events. This condition can affect athletes’ focus, emotional stability, and mental readiness to perform at their best. One technique that is not pharmacological has the potential to lessen feelings of anxiety is the consumption of dark chocolate, which contains bioactive compounds such as flavonoids, tryptophan, and magnesium that play a role in mood regulation. This research sought to ascertain the impact of consuming 70% dark chocolate on the anxiety levels of taekwondo athletes in Bondowoso prior to participating in a belt promotion test. The study employed a randomized controlled trial design involving 60 athletes who were split up into an experimental group and a control group. The analysis results showed that the reduction in anxiety scores in the group consuming dark chocolate was greater than in the control group, with a mean difference of 7,43 in the experimental group and 2,90 in the control group (p = 0,000). These findings indicate that consumption of dark chocolate with 70% cocoa content has an effect on reducing anxiety levels among Bondowoso taekwondo athletes facing promotion tests.